Handling and Control of Floods in the Pulukan River/Tukad Macro Drainage System in Jembrana Regency - Arsana, I Gusti Ngurah Kerta; Astiti, Sagung Putri Chandra (ASTONJADRO, 2023)
Handling and controlling floods in the river/Tukad macro drainage system as the main discharge is a very complex matter. The engineering dimension (engineering) involves many disciplines. In this study, the analytical review is only on hydrological boundaries, hydraulics, watershed erosion, river engineering, morphology, river sedimentation, handling engineering, and flood control systems. The stages of compiling this research were preceded by the collection of secondary and primary data which were then carried out by analysis. The analysis in this planning is carried out qualitatively, quantitatively, and descriptively. The qualitative description focuses on inventorying the drainage system, determining the zoning of the drainage system based on watershed boundaries, class, and identification of area/area per unit drainage system. The quantitative analysis focuses on hydrological and hydraulic calculations as well as a detailed design of each segment of the drainage channel by the service area of ​​each drainage system. Furthermore, the descriptive analysis focuses on determining the priority scale for the handling of the drainage system which is considered vulnerable to flood hazards in the downstream area. Besides that, it also provides technical and non-technical recommendations for flood management. The results of the analysis of the sedimentation rate of the Pulukan River/Tukad 384.726 tons/ha/year are included in the class of severe erosion hazard because most of the community gardening activities are at an elevation of 25% to 40% which has an impact on the high LS slope factor. The existing cross-sectional capacity of the Pulukan River/Tukad is not able to accommodate the flood discharge planned for a return period of 50 years. From the results of this analysis, it is necessary to carry out flood handling/control using structural and non-structural methods. The Tukad Pulukan Watershed flood management and control program includes; reforestation, river normalization work, river management building, Tukad Pulukan watershed management, community-based watershed management, land use regulation, construction of access road inspections, installation of recording of water level and density of recording stations rainfall.